Managing at source and at scale: The use of geomorphic river stories to support rehabilitation of Anthropocene riverscapes in the East Coast Region of Aotearoa New Zealand - Fuller, Ian C.; Brierley, Gary J.; Tunnicliffe, Jon; Marden, Mike; McCord, Jacqui; Rosser, Brenda; Hikuroa, Dan; Harvey, Khendra; Stevens, Elliot; Thomas, Megan (Frontiers in Environmental Science, 2023)
Recently uplifted, highly erodible rocks, and recurrent high intensity storms, generate exceedingly high erosion and sedimentation rates in the East Coast Region (Tairāwhiti) of Aotearoa New Zealand. Despite the recent nature of the Anthropocene record in global terms (∼650 years since Māori arrival, 250 years of colonial impacts), human disturbance has profoundly altered evolutionary trajectories of river systems across the region. Here we document catchment-by-catchment variability in anthropogenic signature as geomorphic river stories for five catchments (Waiapu, Hikuwai, Waimatā, Waipaoa, Mōtū). We show how targeted, fit-for-purpose process-based rehabilitation programmes that manage at source and at scale are required to facilitate river recovery in each of these catchments. The largest rivers in the region, Waiapu and Waipaoa, comprise steep, highly dissected terrains that are subject to recurrent hillslope failures, including systemic shallow landslides, occasional deep-seated rotational slumps and earthflows. Localised sediment input from large (>10 ha) gully mass movement complexes overwhelms valley floors. Targeted revegetation programmes are required to reduce extreme sediment inputs from these sources. Although there are fewer gully complexes in the Hikuwai, multiple landslips supply vast volumes of fine-grained sediment that aggrade and are recurrently reworked along channel margins in lowland reaches. Waimatā has no gully complexes and a smaller number of landslips, but large areas are subject to sediment input from earthflows. The terrace-constrained flume-like nature of this system efficiently flushes materials ‘from the mountains to the sea’, recurrently reworking materials along channel banks in a similar manner to the lower Hikuwai. Systematic reforestation in the middle-upper catchment and revegetation of riparian corridors is required to reduce sedimentation rates in these catchments. In contrast, terraces buffer sediment delivery from hillslopes in the upper Mōtū catchment, where a bedrock gorge separates large sediment stores along upper reaches from the lower catchment. As reworking of valley floor sediments in response to bed incision and reworking (expansion) of channel margins is the primary contemporary sediment source in this system, bed control structures and revegetation of riparian corridors are required as part of targeted sediment management plans. We contend that geomorphic river stories provide a coherent platform for Anthropocene rehabilitation strategies that work with the character, behaviour and evolutionary trajectories of river systems. Although this generic lens can be applied anywhere in the world, we highlight particular meanings and implications in Aotearoa New Zealand where such thinking aligns directly with Māori values that respect the mana (authority), mauri (lifeforce) and ora (wellbeing) of each and every river.